Perancangan Universal Kitchen Cabinet (Studi Kasus Untuk Pengguna Kursi Roda Dan Pengguna Normal) - Sunjaya Hadi (Intra, 2018)
Kitchen is one of the important areas in a house, mainly used to prepare and cook food. Just as cooking has evolved from a food preparation activity to an entertainment activity, the kitchen has also evolved beyond its traditional function. Accommodating these changes requires a deep understanding of each component of the kitchen and its accessibility, both for normal users as well as for the disabled and wheelchair users. In this research, the ethnographic method of study was used to observe and understand disabled users better. The design resulted adopts a modular system so that users can locate and adjust each module according to their space and needs. These modules are separated, so users can fit them according to their needs. The modules consist of a storage module unit which can be reached by the two types of user, an adjustable work station because these two types of users have different ergonomic reach, and a sink that is adjusted to a universal measurement to ensure comfort of use.